Teaching English For Young Learner In Tanah Ombak Community - Wilona, Lidya (STBA PRAYOGA PADANG, 2018)
This article aims to identify how the realization of teaching English for children in Tanah Ombak Community is. This study focuses on what activities that were used by volunteers of STBA Prayoga to teach children in Tanah Ombak Community. The writer hopes that this paper will give beneficial input for readers to know about how to teach English for young learners.Keywords : Activities, English for children in Tanah Ombak Community